Lynch Syndrome - Wulandari, Catharina Endah (PT. Kalbe Farma Tbk., 2014)
Colorectal cancer (CRC) is one of three most common cancer in Indonesia. More than 5% CRC cases are associated with inherited gene mutation called Lynch Syndrome. Lynch syndrome is caused by a germline mutation in a mismatch repair gene (MMR) gene (MLH1, MSH2, MSH6, and PMS2). Individual with these gene mutation have approximately 60 to 80% life-time risk for developing CRC. Lynch syndrome is also related to increased risk of other cancers such as cancers of the endometrium, ovary, stomach, small intestine, hepatobiliary tract, urinary tract, brain, and skin. Lynch syndrome is diagnosed based on family history according to criteria of National NCCN, immunohistochemistry and genetic testing. Identification of people who are predisposed to hereditary colorectal cancer is very important, to allow clinicians assess the effective prevention, early detection and intervention to decrease morbidity and mortality.Kanker kolorektal (KKR) merupakan satu dari tiga kanker terbanyak di Indonesia. Lebih dari 5% kasus KKR berkaitan dengan mutasi gen yang diturunkan yang disebut sebagai sindrom Lynch. Sindrom Lynch disebabkan oleh mutasi germline pada gen mismatch repair (MMR) yang meliputi MLH1, MSH2, MSH6, dan PMS2. Individu dengan mutasi gen tersebut memiliki 60 - 80% life-time risk untuk KKR. Sindrom Lynch juga berhubungan dengan peningkatan risiko kanker lain seperti kanker endometrium, ovarium, gaster, usus halus, traktus hepatobilier, traktus urinarius, otal dan kulit. Sindrom Lynch didiagnosis berdasarkan data riwayat keluarga sesuai kriteria NCCN, pemeriksaan imunohistokimia dan pemeriksaan genetika. Indentifikasi individu pengidap sindrom Lynch sangat penting untuk pencegahan, skrining, dan intervensi dini, dan untuk menurunkan angka mortalitas dan morbiditas.Â